Synthesis of highly c-axis-oriented ZnO thin films using novel laser-enhanced electrospray CVD under atmospheric pressure. Issue 40 (28th September 2017) - Suehiro, Satoshi; Kimura, Teiichi; Yokoe, Daisaku; Takahashi, Seiji
Abstract : Novel process for synthesizing c -axis-oriented ZnO films by novel laser enhanced electrospray CVD. Abstract : Highly c -axis-oriented ZnO nanostructured thin films were deposited by laser-enhanced electrospray chemical vapor deposition (laser ES-CVD) using alcohol-based solutions under atmospheric pressure. ZnO thin films are composed of c -axis-oriented single-crystalline ZnO columnar structures that grow perpendicular to the substrate on an upper ZnO polycrystalline layer. The morphologies drastically changed from sparse dendritic to dense columnar as a result of the addition of glacial acetic acid to the source solutions. The ZnO thin films had a good optical transmittance of more than 80% and an optical band gap of approximately 3.2 eV. ZnO columnar dense films had the highest Hall mobility, for which the carrier concentration was estimated to be 3.3 × 10 17 cm −3 while the resistivity was approximately 9 Ω cm. This result suggests that the ZnO deposition process could be applied to practical material deposition.